The Effect of Genotype x Environment Interaction on Stability Performance for Bread Wheat Genotypes at Diverse Locations - منصور هبه; بولص خوري (Latakia University Journal -Biological Sciences Series, 2023)
Nineteen genotypes of Bread Wheat (Triticum aestivum L.) were tested at four diverse locations in Syria during the 2020-2021season under rain-fed conditions. To evaluate these genotypes and study the Genotypes x Environments Interactions, and stability performance across environments using 6 statistical measures of stability: X¯i, bi, and S²d̅i according to Eberhart and Russell (1966), Stability Variance Index (s 2 i) according to Wricke and Weber (1980), Ecovalance Stability Index (Wi) according to Wricke (1962), and Coefficient of Determination (r2i) according Pinthus (1973) . Genetic material included 13 promising lines and 6 local varieties (provided by ACSAD and GCSAR).The experiment was designed using randomized complete block design with three replications, statistical data analysis was done, and least significant difference (L.S.D) test at 5% was applied for comparison of means. Significant differences were observed among bread wheat genotypes. Combined analysis of variance of grain yield across the four locations showed significant mean squares due to genotypes, environments and genotypes x environments interaction, suggesting differential responses of genotypes across studied environments and validity of stability analysis. Stability analysis for grain yield revealed that; the promising line DOMA66241, ACSAD-1147 and Doma6 were more stable than other genotypes. Due to they had superior ranks for both average yield over environments and yield stability, While the promising line ACSAD1304 showed tolerance to unfavorable environmental conditions, which reveals the importance of invest these genotypes to reach varieties that combine relatively high yield and adapted to a wide range of environmental changes in any future breeding programs.